Development of the human pancreas and its exocrine function - Mehta, Vijay; Hopson, Puanani E.; Smadi, Yamen; Patel, Samit B.; Horvath, Karoly; Mehta, Devendra I. (Frontiers in Pediatrics, 2022)
The pancreas has both endocrine and exocrine function and plays an important role in digestion and glucose control. Understanding the development of the pancreas, grossly and microscopically, and the genetic factors regulating it provides further insight into clinical problems that arise when these processes fail. Animal models of development are known to have inherent issues when understanding human development. Therefore, in this review, we focus on human studies that have reported gross and microscopic development including acinar-, ductal-, and endocrine cells and the neural network. We review the genes and transcription factors involved in organ formation using data from animal models to bridge current understanding where necessary. We describe the development of exocrine function in the fetus and postnatally. A deeper review of the genes involved in pancreatic formation allows us to describe the development of the different groups (proteases, lipids, and amylase) of enzymes during fetal life and postnatally and describe the genetic defects. We discuss the constellation of gross anatomical, as well as microscopic defects that with genetic mutations lead to pancreatic insufficiency and disease states.